Bureaucratic Meritocracy through Talent Management Implementation in Filling Supervisory and Administrative Positions in Balikpapan City Government - Hendra Wardana; Aji Ratna Kusuma; Kus Indarto (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2026)
This study examines the implementation of talent management in filling supervisory and administrative positions within the Government of Balikpapan City, focusing on its role in operationalizing bureaucratic meritocracy. Using a qualitative approach with a case study strategy, the research explores how merit-based principles are translated into practice and identifies the dynamics influencing decision-making processes. Data were collected through in-depth interviews, documentation, and observation, and analyzed using a descriptive qualitative method. The findings indicate that talent management has been formally adopted through instruments such as competency mapping, performance appraisal, and talent pools; however, its implementation remains inconsistent, revealing a gap between procedural frameworks and substantive outcomes. Non-merit factors, including seniority, informal networks, organizational loyalty, and political considerations, continue to influence decisions, resulting in a hybrid form of meritocracy shaped by the interaction between formal systems and socio-political realities. Position filling emerges as a critical locus where meritocratic principles are tested, as it represents the stage at which competing considerations are negotiated and translated into actual decisions. The study underscores the importance of leadership commitment, institutional capacity, and organizational culture in ensuring the effectiveness of merit-based systems. Strengthening these dimensions is essential to transform meritocracy from a procedural requirement into a substantive practice that promotes fairness, professionalism, and organizational performance, while contributing to broader public sector reform at the local government level.